ℋ∞ Performance and Stability Analysis of Linear Systems with Interval Time-Varying Delays and Stochastic Parameter Uncertainties. (23rd February 2015) - Park, M. J.; Kwon, O. M.; Park, Ju H.; Lee, S. M.; Cha, E. J.
Abstract : This paper deals with the problems ofℋ ∞ performance and stability analysis for linear systems with interval time-varying delays. It is assumed that the parameter uncertainties are of stochastic properties to represent random change of various environments. By constructing a newly augmented Lyapunov-Krasovskii functional, less conservative criteria of the concerned systems are introduced with the framework of linear matrix inequalities (LMIs). Four numerical examples are given to show the improvements over the existing ones and the effectiveness of the proposed methods.